Prediction of the tropospheric scintillation for earth to satellite link in tropical climate - Rahim, Nadirah Abdul; Dao, Hassan; Islam, Md. Rafiqul; Ibrahim, Ahmad Fadzil Ismail (2011)
There are many phenomena that cause losses to signal during transmission through the earth's atmosphere. One of them is scintillation. Scintillation arises from atmospheric refractive index discontinuities and resulting in random fades and fluctuation of the received signals amplitude about a mean level. This is caused by small scale loopholes in the transmission path with time. It is an important source of degradation especially on low availability satellite communications systems operating at frequencies above 10GHz. Scintillation occurs continually, nonetheless whether the sky is clear or rainy. Many prediction models have been proposed to predict the tropospheric scintillation which is the fast fluctuations on line of site links on earth-space paths at different frequencies. Most of them can predict tropospheric scintillation from 7 GHz to 20 GHz. All of them have been developed based on scintillation data collected from temperate climate. But tropical countries have different patterns of climate compared to the four seasons' countries. Their climate is mainly uniform temperature, high humidity and heavy rainfall. Up to now, there have been very few researches done on scintillation fit for tropical countries. Hence, scintillation models need to be investigated based on scintillation data measured in tropical country. The purpose of this paper is to investigate on which models are suitable for Malaysia's tropical climate. This paper will also present a complete analysis of all prediction models. It highlights their strengths and limitations and also focuses their suitability to tropical climate.